2019
DOI: 10.1002/we.2419
|View full text |Cite
|
Sign up to set email alerts
|

A new tip correction for actuator line computations

Abstract: The actuator line method (ALM) is today widely used to represent wind turbine loadings in computational fluid dynamics (CFD). As opposed to resolving the whole blade geometry, the methodology does not require geometry-fitted meshes, which makes it fast to apply. In ALM, tabulated airfoil data are used to determine the local blade loadings, which subsequently are projected to the CFD grid using a Gaussian smearing function. To achieve accurate blade loadings at the tip regions of the blades, the width of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 39 publications
3
43
0
Order By: Relevance
“…In this work in particular, for stability reasons, the relationship between the lift coefficient CL,i and the angle of attack is assumed to be linear, , = ⋅ 4. under-relaxation is applied, Γ , = Γ + ⋅ (Γ , − Γ ), with D = 0.05 [20] Steps 2-4 are repeated until the circulation error Γ , − Γ is reduced below a certain tolerance, here taken as 10 -3 . It must be noted that the procedure described so far, in contrast with the original work of Dağ and Sørensen [9], does not account for the contribution of the vorticity shed in the wake. For Darrieus machines in fact, the vortex lines shed by the blades tend to self-intersect as the wake develops downstream, making the evaluation of the corresponding induced velocity extremely challenging.…”
Section: Glauert Correction the Glauert Correctionmentioning
confidence: 94%
See 3 more Smart Citations
“…In this work in particular, for stability reasons, the relationship between the lift coefficient CL,i and the angle of attack is assumed to be linear, , = ⋅ 4. under-relaxation is applied, Γ , = Γ + ⋅ (Γ , − Γ ), with D = 0.05 [20] Steps 2-4 are repeated until the circulation error Γ , − Γ is reduced below a certain tolerance, here taken as 10 -3 . It must be noted that the procedure described so far, in contrast with the original work of Dağ and Sørensen [9], does not account for the contribution of the vorticity shed in the wake. For Darrieus machines in fact, the vortex lines shed by the blades tend to self-intersect as the wake develops downstream, making the evaluation of the corresponding induced velocity extremely challenging.…”
Section: Glauert Correction the Glauert Correctionmentioning
confidence: 94%
“…Dağ-Sørensen (DS) correction. The Dağ-Sørensen correction is based on the observation that, when using an isotropic Gaussian smearing function, the insertion of ALM forces has the same effect on the local flow field of a Lamb-Oseen vortex with a viscous radius equal to the force projection width β [9]. The same vorticity pattern is propagated to the vortex sheet developing in the airfoil wake, which is responsible for the downwash effect commonly associated to tip vortexes.…”
Section: Glauert Correction the Glauert Correctionmentioning
confidence: 99%
See 2 more Smart Citations
“…It must be noted how, since the ALM already resolves the full three dimensional flow field around the actuator line, the use of a tip loss correction might seem redundant. In many studies [17][18][19] however, it has been observed how the base ALM formulation alone is unable to account for this effect, probably because of the use of the regularization kernel to insert the volume forces into the domain. Therefore, its adoption is justified in this work.…”
Section: Hawt Modelmentioning
confidence: 99%